Analisis ketersediaan ruang terbuka hijau dan dampaknya bagi warga kota DKI Jakarta - Harahap, Insan Harapan (Journal of Entrepreneurship, Management and Industry (JEMI), 2021)
This research is entitled analysis of the availability of green open space (RTH) and its impact on the citizens of DKI Jakarta with the aim of seeing the efforts of the DKI Jakarta Regional Government in providing RTH at least 30% from outside its area, which is the mandate of Law Number 26 of 2007 concerning Spatial Planning and DKI Jakarta Regional Regulation Number 1 of 2012 concerning Spatial Planning in 2030. This research is descriptive with a qualitative approach. The data used in this study are secondary data in the form of data and information on green open space in the city of DKI Jakarta, information from the official website, and the results of previous research related to green open space and its impact. The results showed that the Government of DKI Jakarta was only able to provide 14.9% RTH, while the time to realize 30% RTH in DKI Jakarta only had 10 years left. As a result, the city of DKI Jakarta has become an uncomfortable city and the citizens of DKI Jakarta are prone to disease due to air pollution and flooding.